Design, synthesis and biological evaluation of spiropyrimidinetriones oxazolidinone derivatives as antibacterial agents. Issue 7 (15th April 2018) - Siddiqui, Asher M.; Sattigeri, Jitendra A.; Javed, Kalim; Shafi, Syed; Shamim, M.; Singhal, Smita; Malik, Zubbair M.
Graphical abstract: Abstract: Gram-positive bacteria are among the most common human pathogens associated with clinical infections which range from mild skin infections to sepsis. Resistance towards existing class of drugs by Gram-positive bacteria including methicillin resistant Staphylococcus aureus (MRSA), Staphylococcus epidermidis (MRSE) and vancomycin resistant enterococci (VRE) is a growing concern. There is an urgent need to discover new antibiotics which are active against resistant strains of Gram positive bacteria. We report herein a novel class of spiropyrimidinetrione oxazolidinone derivatives as novel antibacterial agents. Key step towards the synthesis of title compounds involved the use of tert -amino reaction with [1, 5]-hydride shift leading to the new CC bond formation. Compound30n has demonstrated potent antibacterial activity against a panel of Gram-positive microbial strains including MRSA, MRSE, and LNZ and vancomycin resistant strains of E. faecalis . Further, molecular docking studies suggest that30n has binding mode similar to that of LNZ in 50S RNA ribosome.